Nilai-nilai Masyarakat Adat Nagari Kapau Kabupaten Agam dalam Perspektif Self-Governing Community - Hasbullah Malau (Jurnal Teori dan Riset Administrasi Publik, 2018)
The implementation of the local government is still a problem at the local level. The Nagari government was built on a structural basis, the model of efficiency, stability, uniformity, and policies towards villages was always changing so that the Indigenous Values ​​were not accommodated as self-governing communities. In fact, Indigenous Values ​​can increase Government democracy. This study aims to describe and analyze the Indigenous Values ​​as a self-governing community in the administration of the Nagari Kapau Government in Agam District. This study uses a qualitative (interactive model of analysis) data reduction, data display, and concrete drawing. Data collection methods by observation, interview, documentation study, and (FGD). The results show that the Indigenous Values ​​of Nagari Kapau are based on history, origin, and continuity of the current Nagari government. As for the Indigenous Values, (1) Ninik Mamak / customary leader, owner of Nagari; (2) Settlement of cases, by Ninik Mamak / Penghulu (3) Islam a single religion; (4) Nagari Conference, Koto Philiang; (5) Government Leader, Wali Nagari; (6) Wali Nagari and Ninik Mamak (Penghulu), Public Service.